Comparative evaluation of Clusia multiflora wood flour, against mineral fillers, as reinforcement in SBR rubber composites (2020)
Clusia multiflora sawdust (CMS) was evaluated as filler in rubber composites. CMS at 40 phr was mixed with synthetic styrene butadiene rubber (SBR 1502), the blend was compatibilized with 8 phr of maleated polyethylene (MAPE). To evaluate the curing and mechanical behavior of CMS, it was compared with precipitated silica (reinforcing filler); calcium carbonate and kaolin (non-reinforcing minerals). The addition of CMS reduced the mechanical properties of rubber compound compared to silica rubber/silica composite. The tensile and tear strength values for SBR/CMS were similar to SBR/CaCO3 and SBR/kaolin. The addition of MAPE to SBR/CMS composite slightly improved the tensile strength, tear strength, abrasion resistance and hardness. In general, CMS performed as diluent filler which reduced the weight of the composite. CMS slightly affected curing speed of SBR/CMS blends. CMS is a waste generated by the use of Clusia multiflora (a timber species endemic of mountains region of Colombia) in the furniture industry. The novelty of this research consists of evaluating the CMS as an alternative to mineral fillers in rubber compounding to improve its mechanical properties, seeking to contribute to the sustainability and to reduce environmental impacts.